(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2023)
This paper presents a comparative analysis of language policy and planning (LPP) in English-speaking countries, exploring the diverse approaches, challenges, and outcomes across different socio-political contexts. Language policy and planning play pivotal roles in shaping linguistic landscapes, educational systems, and societal dynamics, influencing language use, attitudes, and identities. Drawing on a range of scholarly literature, governmental documents, and empirical studies, this comparative analysis examines the multifaceted dimensions of LPP, encompassing official language policies, language-in-education policies, language rights, language maintenance, and language revitalization efforts. The selected English-speaking countries under scrutiny include but are not limited to the United States, United Kingdom, Canada, Australia, and New Zealand, each with its unique historical, cultural, and linguistic heritage. Key themes explored in this analysis include the tension between linguistic diversity and linguistic hegemony, the impact of globalization and immigration on language policies, the role of language ideologies and attitudes in shaping policy decisions, and the intersectionality of language policy with issues of social justice, equity, and inclusion. By critically examining the similarities and differences in LPP approaches among English-speaking countries, this paper aims to elucidate the complex interplay of factors influencing language policies and their implications for linguistic diversity, social cohesion, and educational equity. Moreover, it seeks to contribute to a deeper understanding of the challenges and opportunities inherent in navigating linguistic diversity within the broader framework of national identity, cultural heritage, and globalization in contemporary societies.